Implementasi Alat Sangrai Kelapa Pengaduk Otomatis untuk Meningkatkan Kuantitas dan Kualitas U-Neulheu - Safriani, Novi; Moulana, Ryan; Wardiah, Wardiah; Nilda, Cut; Noviasari, Santi (JURNAL PENGABDIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (JP3L), 2024)
Roasted coconut (U-Neulheu) is one of the typical spices of Acehnese cuisine. U-Neulheu products are mainly produced by home industries in Aceh, one of which is the U-Neulheu Ruwaida micro business, which is a partner in this community service activity. The production process of U-Neulheu is generally carried out traditionally using makeshift equipment, and the roasting process is done manually using a regular frying pan. This results in suboptimal quantity and quality of U-Neulheu products. The purpose of this service activity was to implement Appropriate Technology in the form of an automatic stirrer coconut roaster to improve the quantity and quality of U-Neulheu products produced by partners, thus increasing their income. This community service activity was conducted through counseling, technology application, and technical guidance. Counseling was done by providing an understanding of the technology to be used. Technology application was carried out by implementing the automatic stirrer coconut roaster for U-Neulheu production. Technical guidance was provided by imparting knowledge on how to use and maintain the applied technology. The implementation of Appropriate Technology is very beneficial for partners as it can increase the quantity and quality of U-Neulheu produced by them. This can be seen in the improved quality of the products, especially in terms of the brighter color of the U-Neulheu produced. Meanwhile, the increase in quantity can be measured by the increased number of products produced.